Report on the 27th ORNAC National Conference: Charting the Future of Perioperative Practice - McLennan‐Robbins, Kim (Operating Room Nurses Association of Canada Journal, 2021)
On behalf of the Operating Room Nuses Association of Canada (ORNAC), and specifically the conference planning committee, I would like to thank all of our nursing colleagues and the vendors who attended this year’s conference – our first ORNAC virtual conference. When we first began planning for the 2021 national conference we were excited about offering another awesome educational experience and welcoming everyone to Victoria, BC. Unfortunately, the Covid-19 pandemic forced us to alter all of our conference and travel plans. However, as all perioperative nurses do, each and every day, we adjusted and adapted to our new situation and planned a virtual conference instead. This was uncharted water for all of us! We faced many challenges, but our team rose to the occasion and our virtual conference was a great success. We had 626 delegates and vendors in attendance over the four days.